Comparative genomics of Leptospira santarosai reveals genomic adaptations in bovine genital strains - Di Azevedo, Maria Isabel Nogueira; Kremer, Frederico; Ezepha, Camila; Greco, João Pedro Gomes; da Silva, Isadora Cosenza Vieira; Bourhy, Pascale; Lilenbaum, Walter (Frontiers in Microbiology, 2025)
Bovine genital leptospirosis (BGL) is a silent and chronic reproductive syndrome associated with reproductive failures that result in animal suffering and substantial financial losses for farmers. Important aspects of the interactions between the host and the pathogen during chronic leptospirosis have been well described in the kidney, but little is known about the genital infection mechanisms. The present study sheds light on the pathophysiology of BGL based on comparative genomic analysis of renal versus genital isolates of Leptospira santarosai genomes, an endemic species on Latin America. A significant number of genes were exclusive of the genital strains, with emphasis on genes associated with cell wall/membrane/envelope biogenesis, mobilome: prophages and transposons, and signal transduction mechanisms. Overall, these gene clusters play crucial roles in bacterial colonization and evasion of the immune response, which can reflect leptospiral tissue tropism to the genital niche. We provide new insights into the pathophysiology of an important and neglected syndrome in bovine, helping to elucidate the evolution of adaptation of leptospires in the genital tract of cows.